Mobile game as a learning aid for C++ control structure / Nur Afiqah Nabilah Noor Aris - Noor Aris, Nur Afiqah Nabilah (2017)
“Mobile game as a Learning Aid for C++ Control Structure” is a mobile game-based learning application that is built for first year students of C++ programming course and students who want to learn about control structure in programming. A finding found that a majority of first year students who undergo computer programming course were found to have problem in understanding computer programming subject. Second problem found is the level of students’ understanding toward control structures such as while, do-while, for, goto is one of the weakest among all sub topics in programming language. The last problem found in this research is some other factors that lead to poor performance in programming are student’s lack of interest to learn and a syllabus that focused too much on theory. The first objective of this application is to design a game to teach the concept of control structure in C++ using the game-based learning. Second objective is to develop the designed application and last objective is to test the usability of the application. This application used the Constructivism learning theories. The game genre applied is adventure game. Usability testing has been conducted to the respondent at UITM Campus Jasin, Melaka. The respondent consists of students of semester one in Bachelor of Computer Science and Diploma in Computer Science. Result shows that the knowledge of the respondent increasing after using this application. The graph from the pre-test and post-test differs a lot in a positive way. Therefore, this application can be improved in the future to have a better result.